Hepaticites (Marchantiophyta) in the Lower Permian Arroyo Totoral Formation (La Rioja Province, Argentina) - Coturel, Eliana Paula (2018)
In this contribution we present the first record of a liverwort from the Arroyo Totoral Formation in the Paganzo Basin. The sample is preserved as a compression, founded in a greenish-gray shale with parallel lamination, associated with gymnosperms. The delicate thallus differentiated into wings and midrib with elongate cells but lacking evidence of air-pores like those developed in complex thalloid liverworts, suggests that the fossil is a simple thalloid liverwort. The lack of reproductive traits restricted the assignation to Hepaticites sp. This record supports the interpretation of local humid conditions and improves the Gondwanan Paleozoic record of Bryophytes.